Controversies Regarding the Management of Carcinoma of the Thyroid Gland (TAJ: Journal of Teachers Association, 2009)
Of all solid cancers presenting in adults, papillary thyroid cancers generally carry best longtermprognosis. However, very little is understood about the molecular pathogenesis of thisneoplasm. Any patient presenting with thyroid nodule-initial work up will be fine needleaspiration cytology (FNAC). Surgical treatment depends on FNA finding, age and clinicalpresentation. After surgical debulking whole body diagnostic scan should be performed whichwill follow the need for radioactive iodine (RAI) ablation therapy. Life long assessment afterablation therapy is needed using serum thyroglobulin (Tg) estimation, whole body scan andmost recent introduction of rTSH by FDA , USA.doi: 10.3329/taj.v16i1.3903TAJ June 2003; Vol.16(1): 39-45